The devil in pew number seven : a true story - Alonzo, Rebecca Nichols; DeMoss, Robert G. (Carol Stream, Ill. : Tyndale Momentum, 2012)
Rebecca Nichols Alonzo recounts the events surrounding her father's murder, describing how a church member who refused to give up control when Robert Nichols took over as pastor tormented and threatened her family, until the night that Rebecca's life was shattered forever.
Walking, crawling, dead or alive -- Once upon a dream -- Shotgun justice in Sellerstown -- The devil's in pew number seven -- Under siege -- Now I lay me down to sleep -- The toughest guy in town -- Holding on to hope -- Hearing voices -- Black Thursday -- Unanswered prayers -- Eight men and four women -- Putting the devil on trial -- Life is hard, but God is good -- No apologies in heaven.
Includes bibliographical references (pages 291-296).
Keywords: Alonzo, Rebecca Nichols; Nichols, Robert; Nichols, Ramona; Free Welcome Holiness Church (Sellerstown, N.C.) -- Biography; Victims of violent crimes -- North Carolina -- Sellerstown -- Biography; Alonzo, Rebecca Nichols; Nichols, Ramona; Nichols, Robert; Free Welcome Holiness Church (Sellerstown, N.C.); Victims of violent crimes; Autobiographies; Case studies